Correction: Cardiorespiratory demands of firearms training instruction and 15m shuttle tests in British law enforcement. - Joseph Warwick; Sophie Cooper; Flaminia Ronca (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0300161.].